Inside Back Cover: Sonochemically‐Induced Reduction of Alkenes to Alkanes with Ammonia (Angew. Chem. Int. Ed. 51/2022). Issue 51 (2nd December 2022) - Humblot, Anaelle; Chave, Tony; Amaniampong, Prince N.; Streiff, Stéphane; Jérôme, François
Abstract : The N−H bond of NH3 can be cleaved within cavitation bubbles, generated by ultrasonic irradiation at a high frequency, leading to the in situ formation of a diimide, which then induces the hydrogenation of alkenes, as reported by François Jérôme and co‐workers in their Communication (e202212719) . Advantageously, this technique does not involve any transition metal and releases N2 as a sole coproduct.